Pengaruh Penetapan Harga, Promosi Penjualan dan Ketersediaan Stok terhadap Volume Penjualan Underwear Yi Xin Ren di H&G Collection Pademangan Jakarta Utara - Annisa Annisa; Yugi Setyarko (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of pricing, sales promotions, and stock availability on sales volume at H&G Collection. In an era of increasingly fierce business competition, companies need to manage marketing strategies effectively to maintain and increase sales. Appropriate pricing can influence product appeal to consumers, planned sales promotions can increase purchasing interest, while maintained stock availability ensures that consumer demand is met without interruption. This study used a quantitative approach with primary data sources obtained through questionnaires. The population in this study was all H&G Collection employees in the marketing, finance, and general administration divisions. The sampling technique used a saturated or census sampling method, where all members of the population were sampled. The number of respondents involved in this study was 37. The research instruments were tested for validity and reliability before being used in data collection. The data obtained were analyzed using SPSS version 19 software. The analysis methods included classical assumption tests, multiple linear regression analysis, t-tests, and F-tests to determine partial and simultaneous effects between variables. The results of the study indicate that the three independent variables, namely pricing (X₁), sales promotion (X₂), and stock availability (X₃), have a significant effect on the dependent variable, namely sales volume (Y). This proves that the right pricing strategy, effective promotions, and optimal inventory management can significantly increase sales volume. This finding implies that H&G Collection management needs to maintain and even improve the quality of the implementation of these three variables in an integrated manner to support sales growth and the company's competitiveness in the market.